Papillary Carcinoma of Breast: Clinicopathological Characteristics, Management, and Survival - Bushra Rehman; Anam Mumtaz; Barka Sajjad; Namra Urooj; Sameen Mohtasham Khan; M. Toqeer Zahid; Huma Mannan; M. Zulqarnain Chaudhary; Amina Khan; M. Asad Parvaiz (International Journal of Breast Cancer)
Objective. To study clinicopathological features, treatment strategies, and prognosis of papillary carcinoma of breast. Material and Methods. Data from 58 patients were retrospectively reviewed from January 2010 to December 2016. Four types of papillary carcinoma (on final resected specimen) were included, i.e., invasive papillary carcinoma (IPC), intracystic (encapsulated) papillary carcinoma (EPC), solid papillary carcinoma (SPC), and papillary DCIS (ductal carcinoma in situ). Various features of the four types were observed and compared. Results. Of the 58 patients, 8 were males (13.7%). The mean age at presentation was 61 years; the mean tumor size was 33 mm. The frequency of each histological type was as follows: IPC (n=22/38%), EPC (n=22/38%), SPC (n=12/20.6%), and papillary DCIS (n=2/3.4%). Only two patients were ER negative (both IPC). HER-2 Neu was positive in 3 patients only, out of which 2 died of progressive disease (one EPC and one IPC). LN metastasis was present in 3 (5%) patients (one in each of 1st three types) and only one died of bone metastasis that was also Her-2Neu positive. All patients underwent upfront surgery except two patients who had synchronous IDC on the contralateral side. Breast conservation surgery (BCS) was performed in 34 (58.6%) and mastectomy in 22 (37.9%) patients. 13 patients did not undergo invasive axillary staging; the rest of 43 (74%) patients did (32 sentinel biopsy and 11 axillary dissection). Chemotherapy was given to 18 patients (31%), mostly to IPC (n=12). Only 2 patients had bone metastasis (one was IPC and one EPC). Cancer-related death was observed in 3 patients. For all groups combined, 5-year OS was 98% and DFS was 92%. Conclusion. Overall, papillary carcinoma of the breast has an excellent prognosis, even though less intense treatment modalities were used. It is still difficult to define the optimum management and avoid overtreatment, given the limited data in the literature.